IMPACT OF PREOPERATIVE GASTROESOPHAGEAL REFLUX ON CLINICAL OUTCOMES AFTER STANDARD LAPAROSCOPIC MINI-GASTRIC BYPASS: stratified analysis and scoring-based evaluation - Matkuliev, U.I.; Abduganiyev, J.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Introduction. The role of gastroesophageal reflux disease (GERD) in determining outcomes after laparoscopic mini-gastric bypass (LMGB) remains a subject of active debate. This study investigates the influence of preoperative GERD on early postoperative recovery, symptom control, and functional effectiveness of standard LMGB using a composite scoring scale. Materials and Methods. A total of 68 patients with morbid obesity who underwent standard LMGB were divided into two subgroups: with GERD (n=32) and without GERD (n=36). Symptom dynamics, food tolerance, need for symptomatic medication, and integrated scores were assessed on postoperative days 3, 7, 14, and 30. Results. Patients with preoperative GERD showed higher rates of reflux symptoms on all evaluation days (up to 68.8% on day 7), lower food tolerance (only 25% by day 30), and significantly greater need for symptomatic therapy (81.3%). Their mean integrated score at day 30 was 23.25±4.1, compared to 29.28±3.5 in GERD-negative patients. Moreover, 53.1% of GERD-positive patients fell into the «unsatisfactory» result category. Conclusion. Preoperative GERD significantly worsens early clinical outcomes of standard LMGB. Stratified analysis confirms that reflux status is a strong predictor of postoperative recovery, and supports the need for individualized surgical planning in this population.